1997
DOI: 10.1093/humrep/12.3.532
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary observations on polar body extrusion and pronuclear formation in human oocytes using time-lapse video cinematography

Abstract: In this study, we have used time-lapse video cinematography to study fertilization in 50 human oocytes that had undergone intracytoplasmic sperm injection (ICSI). Time-lapse recording commenced shortly after ICSI and proceeded for 17-20 h. Oocytes were cultured in an environmental chamber which was maintained under standard culture conditions. Overall, 38 oocytes (76%) were fertilized normally, and the fertilization rate and embryo quality were not significantly different from 487 sibling oocytes cultured in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
222
1
14

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(248 citation statements)
references
References 4 publications
11
222
1
14
Order By: Relevance
“…The possibility to analyze the dynamic nature of embryo development gives rise to expectations of improved embryo selection. Time-lapse monitoring enables registration of dynamic events such as the precise timing and synchrony of cell-divisions, appearance and disappearance of nuclei and pro-nuclei; events that in descriptive studies have shown correlation with developmental competence of both animal and human embryos [18,30,41]. In this study, we demonstrate that time-lapse monitoring can be applied safely to human embryos, thereby enabling further investigation of a promising tool for improved embryo selection.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The possibility to analyze the dynamic nature of embryo development gives rise to expectations of improved embryo selection. Time-lapse monitoring enables registration of dynamic events such as the precise timing and synchrony of cell-divisions, appearance and disappearance of nuclei and pro-nuclei; events that in descriptive studies have shown correlation with developmental competence of both animal and human embryos [18,30,41]. In this study, we demonstrate that time-lapse monitoring can be applied safely to human embryos, thereby enabling further investigation of a promising tool for improved embryo selection.…”
Section: Discussionmentioning
confidence: 70%
“…There is a well-documented correlation between embryo morphology evaluated at certain time-points and embryo competence as reviewed in a recent consensus paper by ALPHA and ESHRE [16]. However, the progressive and dynamic nature of cell cleavage and embryo development is also well known [13,18,30], and embryo scoring can change markedly within few hours [25]. In conventional morphological evaluation of embryo quality the number and duration of inspections outside the incubator must be restricted since changes in environment are known to induce stress [42].…”
Section: Discussionmentioning
confidence: 99%
“…Pronuclear fusion was not observed in an investigation using time-lapse cinematography from the appearance of 2PN until syngamy [24]. The following three patterns could be considered for the formation of 3PN zygotes: (1) polyspermy normally occurs only in IVF cases; however, it might be possible in rare cases that a diploid spermatozoon was chosen in ICSI; (2) failure of the 2nd PB extrusion in both IVF and ICSI cycles; and (3) fertilization of a diploid oocyte in IVF or ICSI [25][26][27][28].…”
Section: Discussionmentioning
confidence: 90%
“…In 1997, Payne et al [13] developed time-lapse video cinematography to overcome the limitations of intermittent observation using still images by providing continuous imaging, in which various cellular events could be distinguished in real time and monitored during the observation period. However, this initial system had a limited observation period of 17-20 h. Based on the original report of Payne et al [13], we developed a new in vitro culture system for high-resolution time-lapse cinematography (hR-TLC) by which clear images of embryonic development could be obtained for a long period of time (up to 5 days) by maintaining optimal culture conditions on the stage of an inverted microscope ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, this initial system had a limited observation period of 17-20 h. Based on the original report of Payne et al [13], we developed a new in vitro culture system for high-resolution time-lapse cinematography (hR-TLC) by which clear images of embryonic development could be obtained for a long period of time (up to 5 days) by maintaining optimal culture conditions on the stage of an inverted microscope ( Fig. 1) [14,15].…”
Section: Introductionmentioning
confidence: 99%